The variation of morphological and functional cardiac manifestation in Fabry disease: potential implications for the time course of the disease - Weidemann, Frank; Breunig, Frank; Beer, Meinrad; Sandstede, Joern; Störk, Stefan; Voelker, Wolfram; Ertl, Georg; Knoll, Anita; Wanner, Christoph; Strotmann, Joerg M. (European heart journal, 2005)
Aims The aim of this clinical cross-sectional study was to investigate the cardiac interrelation of morphological and functional abnormalities in patients with Fabry disease. Methods and results Fifty-one patients (5–78 years) were compared with 25 controls (8–77 years). In all subjects, end-diastolic thickness of the left ventricle was measured by echocardiography and ultrasonic peak systolic strain rate (SR) was extracted to assess regional myocardial function. Magnetic resonance imaging was performed to assess late-enhancement for the detection of myocardial fibrosis in Fabry patients (n=39). In patients, women <20 years of age had no hypertrophy, no late-enhancement, and normal radial and longitudinal function (SR longitudinal=−1.7±0.5 s−1; P=n.s. compared with controls). Ten women, >20 years of age, had no hypertrophy, no late-enhancement, normal radial and longitudinal function in the septal wall, but reduced longitudinal function in the lateral wall (SR=−1.4±0.5 s−1). All male patients without hypertrophy and no late-enhancement had normal radial function but reduced longitudinal function in both the septal and lateral walls (SR=−1.3±0.3 s−1). Patients with hypertrophy but without late-enhancement (n=13) had reduced radial and longitudinal function. Twelve patients displaying hypertrophy and late-enhancement had severely reduced radial and longitudinal function (SR=−1.1±0.5 s−1). Two of them with the worst impairment of regional function (SR=−0.8±0.6 s−1) died in the follow-up period. Conclusion These results illustrate the variation of morphological changes and its functional consequences in Fabry cardiomyopathy.